Teaching Materials Design for Cultural Diversity in Samarinda - Marfuah, Siti; Azmi, Muhammad; Rahuma, Aulia; Ramadhan, Andri; Elisa, Elisa (Yupa: Historical Studies Journal, 2025)
Abstract This study aims to design teaching materials that represent the cultural diversity in Samarinda using a design research method. This research focuses on expert evaluation to measure the product's feasibility. The results from the expert evaluation indicate that the developed teaching materials have a high level of cultural relevance and accuracy. However, some improvements were recommended, such as using the more inclusive term "ethnic groups" and adding more culturally representative images. In terms of language clarity, the materials received a perfect score, deemed easy to understand and aligned with linguistic standards. The educational effectiveness was rated favorably, with suggestions to incorporate interactive elements like project-based activities to enhance student engagement, in line with the Merdeka Curriculum. The sequential structure of the content was also highly praised for supporting a structured learning process. Overall, the experts concluded that the teaching materials are highly suitable and viable as a learning resource to promote the understanding and appreciation of cultural diversity among students.